Analisis del indice de morosidad de la cartera de clientes y su incidencia en la rentabilidad de la caja Piura - agencia Huamachuco años 2006-2010. - Gomez Valderrama, Irma (2011)
Bad debt has become the main cause of the difficulties they have experienced some financial systems and certain entities of considerable size. Thus, a high nonperforming loans is a serious problem that involves both the viability of the institution in the long run as the system itself. This research aims to analyze how the default affects on the profitability of The Piura Box - Huamachuco Agency 2006-2010? This was used longitudinal descriptive design time and descriptive analytical method, based on the technique of observation data collected from documentary review of the institution. It was noted that the loan portfolio have increased year after year, reaching 513% growth from 2006 to 2010. But is that a delinquency in the portfolio has increased by 2.851% over the 2006 to 2010, which is very high arrears. Getting a negative return in 2010. Profitability of placements depends on the level of delinquency in each agency. Limit growth in delinquencies while minimizing credit risk, to prevent the growth of supplies and not affect profitability. The credit quality ensures a healthy growth of the placements. This is achieved with a professional and ethical work of its credit assessments, and all officials involved.